Massive hemoperitoneum in case of large subserosal fibroid- a rare case report - Jadeja, Yuvrajsingh Digvijaysingh; Shukla, Radha; Vaishnav, Smruti; Patel, Molina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Rupture of veins on the surface of uterine leiomyoma is an extremely uncommon gynaecological cause of haemoperitoneum. It is a life-threating emergency. In most cases, bleeding is a result of trauma or torsion. Here we report a case of massive intraperitoneal haemorrhage due to rupture of vessels on the surface of large sub-serous leiomyoma to stress on the fact that a differential diagnosis of rupture of surface vessels in a fibroid should be considered while dealing with a case of haemoperitoneum with pelvic masses